Is there an economic consensus? : an attitude survey - Brittan, Samuel (London: Macmillan, 1973)
The objective of the enquiry discussed in this book is to examine the importance of both the unifying and the divisive factors among the policy views of professional economists, by comparison with the views of politicians and others.
Includes bibliographical references.
rpm 22/06/2017
Loans
Keywords: Economic policy; Economists; Economists $1 (BGreat Britain.s; Great Britain $1 (BEconomic policy $1 (B1964-s; Great Britain $1 (BEconomic policy $1 (B1964-1979.s; Great Britain $1 (BEconomic policy $1 (B1945s; Great Britain $1 (BEconomic policy $1 (B1945-1964s; Great Britain